The relation between pre-eclampsia at term and neonatal encephalopathy. Issue 3 (1st November 2001) - Impey, L; Greenwood, C; Sheil, O; MacQuillan, K; Reynolds, M; Redman, C
Abstract : OBJECTIVES: To determine whether pre-eclampsia, hypothesised to be an inflammatory condition, is associated with fever in term labour, and confirm and examine the reported association of pre-eclampsia at term with neonatal encephalopathy. DESIGN: Prospective cohort study. SETTING: A Dublin teaching hospital. PARTICIPANTS: 6163 women in labour with singleton pregnancies at term at low risk for intrapartum hypoxia, recruited to a randomised trial examining the effect of admission cardiotocography on neonatal outcome. RESULTS: Pre-eclampsia was associated with maternal fever > 37.5° in labour (odds ratio (OR) 3.39, 95% confidence interval (CI) 2.1 to 5.4); this was independent of obstetric intervention (adjusted OR 2.07, 95% CI 1.24 to 3.47). Pre-eclampsia was associated with neonatal encephalopathy (OR 25.5, 95% CI 8.4 to 74.7); this too was independent of obstetric intervention (adjusted OR 18.5, 95% CI 5.9 to 58.1). Cord arterial pH values were significantly lower in pre-eclamptics (7.20 v 7.24), although severe cord acidaemia was not significantly more common (OR 2.91, 95% CI 0.7 to 9.9). The association of pre-eclampsia with encephalopathy was independent of maternal fever (adjusted OR 16.5, 95% CI 5.1 to 54) and cord acidaemia (adjusted OR 13.5, 95% CI 3.2 to 56.7). CONCLUSIONS: The association of pre-eclampsia with maternal fever at term supports the hypothesis that pre-eclampsia is an inflammatory condition. The association of pre-eclampsia with neonatal encephalopathy is independent of obstetric intervention and cannot be explained by either acidaemia or maternal fever. A systemic inflammatory response in the fetus, perhaps secondary to oxidative stress, could explain the link between maternal pre-eclampsia and neonatal encephalopathy, and this may occur through cerebral vasoconstriction.